Assessing the Educational and Supportive Care Needs of Canadian Metastatic Melanoma Patients and Survivors Attending an Outpatient Clinic. (21st July 2021) - Subasri, Mathushan; Lemonde, Manon; Mundluru, Jahnavi; Chang, Jose; Koneru, Rama
The rapid development of metastatic melanoma treatment options has significantly improved overall survival, but paralleled patient educational and supportive care resources have fallen behind. Particularly, the need for grassroots programs targeting environments outside urban centers has grown. Accordingly, an environmental scan of the Durham region in Ontario, Canada, showed the lack of melanoma-specific resources for outpatients. The goal of this study was to identify the needs of metastatic melanoma patients and survivors attending a large outpatient clinic in Durham, and then develop a patient-reviewed intervention plan. Needs were assessed in 5 domains through a melanoma-specific supportive care needs assessment survey. Among 75 surveyed melanoma patients and survivors, high-level needs were identified in 3 domains: psychological, health system information, and melanoma-specific information. Furthermore, domain-specific needs were heightened in specific sociodemographic groups. Based on these survey results, a multifaceted intervention plan was developed to mitigate future needs. The intervention plan was patient-reviewed in focus groups prior to implementation, refining the developed intervention plan.